Competency requirements of academic librarians in providing research data management services: the case of two university libraries - Badenhorst, Patricia (Library and Information Studies Centre (LISC), 2023)
The objective of this study was to identify, using the Mangosuthu University of Technology (MUT) and the University of KwaZulu-Natal (UKZN) libraries as case studies, the competency requirements of academic librarians in providing research data management services. The following research questions guided the study: What knowledge, skills and other competencies do librarians at MUT and UKZN currently possess to support research data management services?; What knowledge, skills and other competencies do academic librarians require in order to effectively provide research data management services to their research communities?; and, What strategies are required to ensure that academic librarians are equipped with the necessary knowledge, skills and other competencies in order for them to effectively provide research data management services to the library's research communities? The study was situated within in an interpretivist paradigm and a qualitative approach was adopted to obtain the in-depth data required from study participants. A multiple case study design was used and the target population included academic librarians from MUT and UKZN. Non-probability purposive sampling was employed to select participants for the study and semi-structured interviews were used to collect data from librarians with different job profiles at the two academic institutions. This data collection was supplemented by document reviews involving content analysis of relevant academic library job advertisements. The study's conclusion presents a blend of knowledge, skills and personal attributes required by academic librarians to support research data management services. It recommends robust training as well as institutional support in various forms in order for academic librarians to upskill for effective provision of data management services (RDM) to their research communities. The study also recommends academic library collaboration and cooperation with relevant institutional departments for effective implementation of RDM services to the university's research communities.